Advanced Engineering Schools as Innovation Hubs in Post-Industrial Higher Education: Institutional, Pedagogical, and Business Model Perspectives - Glushchenko, Valery Vladimirovich (ASEAN Journal of Educational Research and Technology, 2025)
This paper examines the role of Advanced Engineering Schools (AES) as key innovation subsystems within post-industrial higher education. Drawing on institutional theory, systems analysis, and creative pedagogy, the study explores how AES integrates scientific research, technological innovation, and educational practices to enhance university competitiveness and national technological sovereignty. The research presents the organizational structure of AES, its business models, customization strategies, and the incorporation of neuro-innovation and personnel development systems. The study also highlights how AES fosters creative pedagogy to prepare graduates for future-oriented professions and contribute to the formation of a national creative class. By integrating research, innovation, and education, AES serves as a dynamic platform for interdisciplinary learning, offering valuable insights for higher education reform globally. The findings contribute to the development of educational models that balance innovation, institutional transformation, and pedagogical creativity in the rapidly evolving landscape of higher education.